Assessment of Radiologic Damage by Larsen Score in Adults With Juvenile Idiopathic Arthritis - Eda Gürçay; Serdil Yüzer; Emel Ekşioğlu; Ajda Bal; Aytül Çakcı (Archives of Rheumatology, 2008)
Objective: Juvenile idiopathic arthritis (JIA) is a heterogenous and chronic disease. The aim of this study was to evaluate radiologic damage, measured by Larsen score, in adults with JIA and to determine disease-related parameters correlated with this score. Materials and Methods: Overall 38 adults identified with JIA at 18 years of age or older with disease duration of at least 5 years were assessed by means of the Larsen hand score. Patients were divided into 3 groups according to disease duration; Group 1 (5-10 years), Group 2 (11-15 years and Group 3 (more than 16 years. Patients were classifed further according to JIA subtypes as seropositive polyarticular (group A), seronegative polyarticular (group B), and oligoarticular (group C). Radiologic damage, articular damage and functional disability were measured by Rheumatoid Arthritis Articular Damage (RAAD) score and Health Assessment Questionnaire (HAQ). Relationship between the Larsen score and disease duration, JIA subtypes, sex, age at onset of the disease, RAAD score and HAQ were investigated. Results: We observed significant difference in the Larsen scores of groups according to JIA subtypes (p<0.001) and female gender (p=0.001) but not in the groups according to disease duration (p>0.05). There was no significant correlation between the Larsen scores and age at onset of the disease (p>0.05). It was observed that the Larsen score correlated well with RAAD and HAQ (p<0.001). Conclusion: Female gender and seropositivity have negative effects on radiologic damage in adults with JIA. Especially for seropositive poliarticular JIA patients, regular follow-up visits and more aggressive treatment approach are recommended. (Rheumatism 2008; 23: 124-8)